Swiss Evaluation Registry for Pediatric Infective Endocarditis (SERPIE) - Risk factors for complications in children and adolescents with infective endocarditis. (1st January 2023) - Schuler, Stefanie Katharina; Crisinel, Pierre Alex; Joye, Raphael; Rohr, Marie; Bressieux-Degueldre, Sabrina; Glöckler, Martin; Paioni, Paolo; Agyeman, Philipp K.A.; Knirsch, Walter
Abstract: Background: Infective endocarditis (IE) in pediatric patients is a severe cardiac disease and its actual epidemiology and clinical outcome in Switzerland is scarcely studied. Methods: Retrospective nationwide multicenter data analysis of pediatric IE in children (<18 years) between 2011 and 2020. Results: 69 patients were treated for definite (40/69;58%) or possible IE (29/69;42%). 61% (42/69) were male. Diagnosis was made at median 6.4 years (IQR 0.8–12.6) of age with 19 patients (28%) during the first year of life. 84% (58/69) had congenital heart defects. IE was located on pulmonary (25/69;35%), mitral (10/69;14%), tricuspid (8/69;12%) and aortic valve (6/69;9%), and rarely on ventricular septal defect (VSD;4/69;6%) and atrial septal defect (ASD;1/69;1%). In 22% (16/69) localization was unknown. 70% (48/69) had postoperative IE, with prosthetic material involved in 60% (29/48; right ventricular to pulmonary artery conduit (24), VSD (4), ASD (1)). Causative organisms were mostly S taphylococci spp. (25;36%) including Staphylococcus aureus (19;28%), and S treptococci spp. (13;19%). 51% (35/69) suffered from severe complications including congestive heart failure (16;23%), sepsis (17;25%) and embolism (19;28%). Staphylococcus aureus was found as a predictor of severe complications in univariate and multivariate analysis ( p = 0.02 and p = 0.033). In 46% (32/69) cardiac surgery was performed. 7% (5/69) died. Conclusions: IE in childhood remains a severe cardiac disease with relevant mortality. The high morbidity and high rate of complications is associated with Staphylococcus aureus infections. Congenital heart defects act as a risk factor for IE, in particular the high number of cases associated with prosthetic pulmonary valve needs further evaluation and therapeutic alternatives. Highlights: SERPIE is the first nation-wide registry for pediatric infective endocarditis in Switzerland Most patients with pediatric infective endocarditis suffered from a congenital heart disease The right ventricular to pulmonary artery outflow tract conduit was mostly infected The most common pathogen for infective endocarditis is Staphylococcus aureus Staphylococcus aureus is significantly associated with severe complications